Efficiency of three different polishing methods on enamel and cementum: A scanning electron microscope study - Zoya Chowdhary; Ranjana Mohan (Wolters Kluwer Medknow Publications, 2018)
Background: Tooth polishing is an integral part of clinical dentistry. The main purpose of polishing is to smoothen the surface of the tooth and minimize the deposition of plaque to allow a healthy periodontal maintenance postscaling. Today, polishing by different methods is available to a clinician. Traditional bristle brush and rubber-cup polishing are being widely practiced and gradually getting replaced by novel air polisher. Pros and cons of each method should be weighed before its clinical applications. Aim and Objectives: To evaluate and compare the efficiency of three different polishing systems on enamel as well as on cementum surfaces by scanning electron microscope (SEM). Materials and Methods: A total of 120 samples were divided into three groups randomly - Group 1 (bristle brush), Group 2 (rubber cup), and Group 3 (air polisher) - with 20 samples each of enamel and cementum, which were subdivided into 10 control and 10 test group (subjected to polishing). The samples were analyzed by SEM at ×1000 magnification, and the data obtained were compiled and subjected to statistical analysis. Results: Polishing with bristle brush demonstrated less surface roughness and debris when compared to air polisher at P = 0.58, P = 0.03 for enamel surface and P = 0.003, P = 0.21 for cementum, respectively. The surface roughness was reduced considerably by rubber cup at P = 0.03 for enamel and P = 0.003 for cementum, compared to air polisher at P = 0.99 and P = 0.21 for enamel and cementum, respectively. Conclusion: The results indicate that polishing with rubber cup was more effective and statistically significant when compared to bristle brush polishing and air polisher for the crown and root surface smoothening and debris removal.